The path of blood in the human body: history of science in the training of in-service biology teachers - Augusto, Thaís Gimenez da Silva [UNESP]; da Silva Junior, Carlos Aparecido [UNESP] (Sociedade Brasileira de Historia da Ciencia, 2020)
The literature points out the importance of the approach of the History of Science so that students better understand the nature of scientific knowledge and how it is produced. However, teachers are rarely trained on this subject. For these reasons, a training course was developed for Biology teachers on History and Philosophy of Science. This article analyzes the results of the meeting that dealt with the history of ideas about blood circulation. This is a qualitative, intervention-type research. The analysis showed that the meeting contributed to a broader view of the history of science in relation to a topic that teachers knew little about.
A trajetória do sangue no corpo humano: a história da ciência na formação continuada de professores de biologia
Keywords: Biology teaching; blood circulation; high school; teacher training